Analysis of Outpatient Repeat Visit Interest using the Marketing Mix Method: Literature Review - Loveni Parenti, Uyun; Prayoga, Diansanto (Jurnal Kesmas Prima Indonesia, 2025)
Hospitals must provide safe, high-quality, and effective health services in accordance with standards, focusing on patient satisfaction and the implementation of appropriate marketing strategies. Through marketing mix analysis, this study aims to analyze the interest in patients' return visits to outpatient services. The objective of this research is to examine whether this marketing mix method can stimulate interest in the return visits of outpatient patients in healthcare services. The method used is a literature review. The results indicate that the "people" aspect of the marketing mix is crucial for the interest in patients' return visits to outpatient services, as the quality of employee service significantly influences patients' perceptions. Effective marketing strategies can enhance patient experience and loyalty. Therefore, the conclusion drawn is that a healthcare service that is friendly, professional, and responsive, along with the marketing mix aspects, greatly affects the interest in patients' return visits. Thus, hospitals need to improve staff training and management systems, as well as conduct regular satisfaction surveys to enhance services and patient satisfaction. Kata kunci : Bauran Pemasaran, Minat Kunjungan Ulang, Rawat Jalan